2019
DOI: 10.1536/ihj.19-313
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Led Collaborative Management Using Telemonitoring Improves Quality of Life and Prevention of Rehospitalization in Patients with Heart Failure

Abstract: The effects of disease management using telemonitoring for patients with heart failure (HF) remain controversial. Hence, we embedded care coordination and enhanced collaborative self-management through interactive communication via a telemonitoring system (collaborative management; CM). This study evaluated whether CM improved psychosocial status and prevented rehospitalization in patients with HF in comparison with selfmanagement education (SM), and usual care (UC). We randomly allocated 59 patients into 3 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 35 publications
3
73
1
5
Order By: Relevance
“…We have developed various nurse-led disease management programs at community-based and collaborating with primary care physicians. [13][14][15][16] We assumed by combining this method with telenursing, it was possible to provide support to encourage SM education to prevent the onset and exacerbation of cardiometabolic risks among residents, even in remote islands with limited medical resources.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed various nurse-led disease management programs at community-based and collaborating with primary care physicians. [13][14][15][16] We assumed by combining this method with telenursing, it was possible to provide support to encourage SM education to prevent the onset and exacerbation of cardiometabolic risks among residents, even in remote islands with limited medical resources.…”
Section: Introductionmentioning
confidence: 99%
“…Daily weight was electronically transmitted in the intervention group in [ 29 ] where the all-cause mortality and HF hospitalization hazard ratios were 0.57 and 0.9, respectively. In addition, in [ 78 ], there was a significant improvement in the intervention group compared to the usual group, where patients used telemonitoring devices to monitor BP, weight and HR over 12 months, achieving a hazard ratio for HF hospitalization of 0.29, which can be seen in Figure 9 b. This figure also shows that in [ 48 ], patients with a positive combined HF device diagnostic have a 4.8-fold increase of HF hospitalization after adjusting for clinical variables.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Therefore, implementing mechanisms that both monitor and encourage daily measurement along with staff enthusiasm toward using the system can help improve adherence. In another study, the nurse-led collaborative management group showed promising results with reductions in readmission rates and improved quality of life compared to usual care [ 78 ]. They suggest the effectiveness of this telemonitoring study was due to the collaborative support by nurses and healthcare workers rather than simply concentrating on physiological parameters.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The results of a meta-analysis of diabetic patients were showed that the use of telenursing (vs. usual care) was associated with a significant reduction in HbA1c levels compared to usual care [12]. Similarly, tele-nursing for patients with heart failure was shown to be effective in improving the QOL of patients, preventing readmission, and improving cost effectiveness [13] [14].…”
Section: Introductionmentioning
confidence: 99%